A self paced treadmill walking test for breathless patients. Issue 6 (June 1985) - Beaumont, A; Cockcroft, A; Guz, A
Abstract : A treadmill exercise test is described that retains the advantages of self paced walking but allows the measurement of cardiorespiratory variables. A horizontal treadmill was modified to allow patients to control their own speed. During exercise continuous measurements of speed, distance, heart rate, arterial oxygen saturation, and stride length were made and subjective assessments of breathlessness were recorded on a visual analogue scale. Ten men with severe chronic obstructive lung disease performed a 12 minute corridor walk and a self paced 12 minute treadmill walk on the same day and repeat treadmill walks on different days. Six of them performed three walks or more. Six patients had ventilatory measurements during treadmill exercise. There was no significant difference (p greater than 0.1) in the distance covered during corridor and treadmill walks, and distances on the treadmill were repeatable after the first walk. Use of a mouthpiece significantly reduced the distance covered on the treadmill. The self paced treadmill walk is a simple repeatable test and has advantages over both a corridor walking test and standard progressive tests for assessment of breathless patients.